Cross-fertilisation, not bifurcation, of EMI and EAP. (9th September 2022) - Galloway, Nicola; Rose, Heath
Abstract: The article responds to Wingate and Hakim's paper, where they criticise English Medium Instruction (EMI) research for not drawing on research and practices from EAP. We concur that this cross-fertilisation of knowledge is beneficial for both fields but emphasise the breadth of the current EMI research agenda, which explores several issues beyond English language and academic preparedness. We also counter their claims of a lack of awareness by highlighting several examples of knowledge exchange, much of which has been driven by EMI scholars working within EAP contexts, and vice versa. Finally, we urge caution in recommendations to uncritically adopt EAP practices from Anglophone university settings into EMI settings, due to the complexities associated with EMI growth and provision, where the challenges raised are not necessarily identical. Overall, we agree with the authors that EAP and EMI have much to gain from each other in their shared endeavours and welcome their calls for future research collaboration.